A Systematic Review of Clinical Guidelines for Preconception Care - Dorney, Edwina; Boyle, Jacqueline A.; Walker, Ruth; Hammarberg, Karin; Musgrave, Loretta; Schoenaker, Danielle; Jack, Brian; Black, Kirsten I. (Seminars in Reproductive Medicine, 2022)
Preconception care (PCC) involves a wide-ranging set of interventions to optimize health prior to pregnancy. These interventions seek to enhance conception rates, pregnancy outcomes, childhood health, and the health of future generations. To assist health care providers to exercise high-quality clinical care in this domain, clinical practice guidelines from a range of settings have been published. This systematic review sought to identify existing freely accessible international guidelines, assess these in terms of their quality using the AGREE II tool, and assess the summary recommendations and the evidence level on which they are based. We identified 11 guidelines that focused on PCC. Ten of these were classified as moderate quality (scores ranging from 3.5 to 4.5 out of 7) and only one was classified as very high quality, scoring 6.5. The levels of evidence for recommendations ranged from the lowest possible level of evidence (III) to the highest (I-a): the highest quality evidence available is for folic acid supplementation to reduce risk of neural tube defects and the role of antiviral medication to prevent HIV transmission. This systematic review identified that high-quality guidelines on PCC are lacking and that few domains of PCC recommendations are supported by high-quality evidence.
Keywords: preconception; pre-pregnancy; clinical practice guideline; policy; systematic review